The Influence of Organizational Culture and Emotional Intelligence on the Employee Performance and with the Employee Engagement as the Mediating Variable - Hermawan, Lisa Bella; Abadi, Ferryal (Universitas Mercu Buana, 2024)
Objectives: The objective of this study is to explore the influence of organizational culture and emotional intelligence on employee performance with employee engagement as a mediating variable.Methodology: This research involved the questionnaire survey of employees at a multi-finance company. The data collected was then analyzed with a structural model approach, using quantitative methods. The population in this study involved 240 employees at a multi-finance company in the Jakarta area.Finding: In the variable of Employee Engagement influenced by the variables of Organizational Culture and Emotional Intelligence, an R-Square value of 0.455 was obtained. This explains that the percentage of the predictor variables, Organizational Culture and Emotional Intelligence, can explain 45.5% of Employee Engagement. In the variable of Job Performance influenced by the variables of Organizational Culture, Emotional Intelligence, and Employee Engagement, an R-Square value of 0.380 was obtained. This explains that the percentage of the predictor variables, Organizational Culture, Emotional Intelligence, and Employee Engagement, can explain 38% of Job Performance.Conclusion: The results indicate that Organizational Culture and Emotional Intelligence in multifinance companies influence Employee Performance, and Employee Engagement has a mediating effect. This research has practical implications for multifinance companies in building Organizational Culture and Emotional Intelligence and increasing Employee Performance through Employee Engagement.